Reviewing the methodology for promoting the awareness of gender equality through ELT materials in industrial revolution 4.0 - Maya Pinkan Warouw; Christy Cherly Rambing (Edumaspul: Jurnal Pendidikan, 2024)
In the wake of transformative alterations in the Industrial Revolution epoch, a discernible transition has transpired, heralding a departure from conventional printed instructional resources to a realm dominated by digitalized pedagogical materials. In light of this evolution, the present investigation aspires to delve into a discerning framework tailored to scrutinize the efficacy of educational media crafted to propagate gender egalitarianism. Methodologically, this qualitative inquiry has harnessed the potency of document analysis as a means to amass pertinent data, augmented by the application of content analysis techniques to dissect the amassed information stemming from both traditional print and contemporary digital teaching media. The study's outcomes elucidate an emergent paradigm derived from the pre-existing evaluative framework, delineating a novel trajectory in discerning gender-centric content within didactic materials. In conclusion, the criteria underpinning this evaluative process extend beyond conventional parameters, encapsulating innovative benchmarks such as progressiveness and neutrality, though not circumscribed exclusively to these classifications. This study thus unveils a nuanced perspective, casting a discerning light on the multifaceted facets of evaluating pedagogical materials in the dynamic milieu of digitalized education